The Indian Yearbook of Comparative Law 2020 - John, Mathew; Devaiah, Vishwas H.; Baruah, Pritam; Tundawala, Moiz; Kumar, Niraj (The Indian Yearbook of Comparative Law, 2023)
XIII, 291 p. 9 illus., 7 illus. in color.